Relative contribution of IL‐1α, IL‐1β and TNF to the host response to Mycobacterium tuberculosis and attenuated M. bovis BCG. Issue 1 (30th September 2013) - Bourigault, Marie‐Laure; Segueni, Noria; Rose, Stéphanie; Court, Nathalie; Vacher, Rachel; Vasseur, Virginie; Erard, François; Le Bert, Marc; Garcia, Irene; Iwakura, Yoichiro; Jacobs, Muazzam; Ryffel, Bernhard; et al.
Abstract: TNF and IL‐1 are major mediators involved in severe inflammatory diseases against which therapeutic neutralizing antibodies are developed. However, both TNF and IL‐1 receptor pathways are essential for the control of Mycobacterium tuberculosis infection, and it is critical to assess the respective role of IL‐1α, IL‐1β, and TNF. Using gene‐targeted mice we show that absence of both IL‐1α and IL‐1β recapitulates the uncontrolled M. tuberculosis infection with increased bacterial burden, exacerbated lung inflammation, high IFNγ, reduced IL‐23 p19 and rapid death seen in IL‐1R1‐deficient mice. However, presence of either IL‐1α or IL‐1β in single‐deficient mice is sufficient to control acute M. tuberculosis infection, with restrained bacterial burden and lung pathology, in conditions where TNF deficient mice succumbed within 4 weeks with overwhelming infection. Systemic infection by attenuated M. bovis BCG was controlled in the absence of functional IL‐1 pathway, but not in the absence of TNF. Therefore, although both IL‐1α and IL‐1β are required for a full host response to virulent M. tuberculosis, the presence of either IL‐1α or IL‐1β allows some control of acute M. tuberculosis infection, and IL‐1 pathway is dispensable for controlling M. bovis BCG acute infection. This is in sharp contrast with TNF, which is essential for host response to both attenuated and virulent mycobacteria and may have implications for anti‐inflammatory therapy with IL‐1β neutralizing antibodies. Abstract : Here, we confirm that both TNF and IL‐1 pathways are required to control M. tuberculosis infection since absence of both IL‐1a and IL‐1ß recapitulated the dramatic defect seen in the absence of IL‐1R1 or TNF. However, presence of either IL‐1a or IL‐1ß allows some control of acute M. tuberculosis infection. Further, although TNF is essential for the early control of infection by either virulent or attenuated mycobacteria, IL‐1 pathway is dispensable for controlling less virulent infection by M. bovis BCG.